2023
DOI: 10.37256/dmt.3120231856
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modeling (BIM) and Robotic Manufacturing Technological Interoperability in Construction – A Cyclic Systematic Literature Review

Abstract: The architectural engineering and construction (AEC) industry is undergoing a digital transformation that progressively improves its performance, productivity, and competitiveness. This digital shift is accelerated through building information modeling (BIM) which facilitates technological integrations. BIM has significantly contributed to digitizing design and management activities. However, it has not yet sufficiently demonstrated its interoperability with digital manufacturing processes, such as robotic man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Anane et al (2023) recently investigated interoperability related to computational design driven by BIM to help bridge the gap between robotics and construction. They found that current tools are insu cient for complex projects and inadequate for data management, nding more work is required to improve the process (Anane et al, 2023). Notably, standards are being developed and maintained by BuildingSMART to support the IFC schema, which is one of the adopted formats for exporting information (Edirisinghe & London, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Anane et al (2023) recently investigated interoperability related to computational design driven by BIM to help bridge the gap between robotics and construction. They found that current tools are insu cient for complex projects and inadequate for data management, nding more work is required to improve the process (Anane et al, 2023). Notably, standards are being developed and maintained by BuildingSMART to support the IFC schema, which is one of the adopted formats for exporting information (Edirisinghe & London, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, formats like IFC support simple models, resulting in missing information when the exchange occurs (Tibaut et al, 2016). Anane et al (2023) recently investigated interoperability related to computational design driven by BIM to help bridge the gap between robotics and construction. They found that current tools are insu cient for complex projects and inadequate for data management, nding more work is required to improve the process (Anane et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, formats like IFC support simple models, resulting in missing information when the exchange occurs [25]. Anane et al [26] recently investigated interoperability related to computational design driven by BIM to help bridge the gap between robotics and construction. They found that current tools are insufficient for complex projects and inadequate for data management,finding more work is required to improve the process [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Anane et al [26] recently investigated interoperability related to computational design driven by BIM to help bridge the gap between robotics and construction. They found that current tools are insufficient for complex projects and inadequate for data management,finding more work is required to improve the process [26]. Notably, standards are being developed and maintained by BuildingSMART to support the IFC schema, which is one of the adopted formats for exporting information [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…BIM is a digital representation of a building's physical and functional characteristics, offering a holistic view of a construction project from inception to completion. When combined with robotic construction techniques, BIM becomes a potent catalyst for innovation, enabling architects, engineers, and builders to optimize the construction process in unprecedented ways [9][10][11][12] .…”
mentioning
confidence: 99%